165 PHARMACIST-LED MEDICINES RECONCILIATION: AN OBSERVATIONAL STUDY TO EVALUATE INFORMATION SOURCES AS A QUALITY INDICATOR OF THE SERVICE. (25th October 2022) - Hadzic, D; Ryan, T; Murphy, D
Abstract: Background: Medicines Reconciliation (MR) involves obtaining a Best-Possible Medication History (BPMH) and is essential for reducing medication errors and adverse events. Recommendations on how best to undertake MR range from utilising the patient alone to using ≥2 sources (in addition to the patient). Few studies evaluate the use of >1 source as a measure of MR quality. Methods: This observational study was undertaken in a major teaching hospital that provides a dedicated pharmacist-led MR service. Eligible patients (aged ≥65 years, admitted through the Emergency Department) were randomly recruited. MRs were compiled using 2 sources and compared to individual 1-source MRs (both in addition to patient/carer interview). Additional Medication Discrepancies (AMDs), or differences between 1-source and 2-source MR, were assessed and potential predictors analysed. Results: A total of 114 patients were included. Community pharmacy was the most frequently used and most accurate source (full agreement in 97.4% of BPMHs). Two-thirds of MRs would not differ if either of the two sources were used in isolation, alongside patient/carer interview. The remaining MRs identified a total of 85 AMDs (1–6 per MR). The majority were drug omissions (49.4%). Most were deemed "low" potential clinical significance (59%). Higher patient/carer reliability was associated with lower incidence (p=0.001) and fewer AMDs (p=0.001). Conclusion: Contrary to some international guidelines, using >1 source (in addition to patient/carer interview) does not add value to the BPMH in the majority of cases.